Evaluation of new oil-dispersible fungicide formulations for the control of abnormal leaf fall of rubber (Hevea brasiliensis) caused by Phytophthora spp - Jacob C K; Idicula S P; Kothandaraman R; Manju M J (Indian Journal of Natural Rubber Research, 2001)
New oil-dispersible fungicide formulations, mancozeb and its combination with copper oxychloride (COC) and metalaxyl in combination with COC were field-tested in different locations for the control of abnormal leaf fall disease of rubber (Hevea brasilienis) caused by Phytophthora spp by aerial and ground spraying. A powder formulation of mancozeb and a combination product of COC andmetalaxyl (5kg/ha) were found to be as effective as COC (8kg/ha). The new fungicides are useful alternatives for COC which has been continuously in use for about four decades.
Keywords: Abnormal leaf fall; Disease control; Hevea; Phytophthora; Spraying